Pengaruh Game Based Learning terhadap Kemampuan Problem Solving Matematika Siswa di MTsN 1 Kutacane - Nadia Hidayati; Yahfizham (Media Pendidikan Matematika, 2025)
The purpose of this study is to examine the effect of implementing the Game-Based Learning (GBL) model on students’ problem-solving abilities in the topic of Linear Equations in One Variable (LEOV) at MTsN 1 Kutacane. This study employs an experimental research method with a pretest-posttest control group design. The research sample consisted of 60 seventh-grade students, divided into two groups: the experimental group, which applied the GBL model using the Wordwall application, and the control group, which used conventional teaching methods. Based on the data analysis results, there was a significant difference in learning outcomes between the two groups, as indicated by a p-value < 0.05. The average N-Gain value for the experimental group was 42.97% with a moderate category, while the control group achieved an N-Gain value of 23% with a low category. Thus, the Game-Based Learning model is effective in improving students’ mathematical problem-solving abilities. Keywords: problem solving, game based learning, wordwall, of linear equation in one variable (LEOV)